Le bien-être au prisme des violences scolaires Espaces, corps, valeurs - Bruneaud, Jean-François; Montoya, Yves; Ben Chaâbane, Zhaïra (S@nté en contextes, 2023)
The school, a reflection of a nation's values and moral standards, is faced with well-being challenges. Through a selection of articles from presentations given within the framework of the Working Group (GT11, which became CR40 in 2022) of the 21st International Congress of the International Association of French-speaking Sociologists (AISLF) held in 2021 in Tunis, this book discusses the school environment, discrimination, and the influence of norms on educational actors. Organized into three parts, it addresses public policies, recognition as a factor of well-being/distress, and interpersonal relationships. The multidisciplinary studies question reductive dogmas and examine school violence from various perspectives. This book illuminates the challenges faced by school and university actors regarding norms, discrimination, and diversity, and offers ideas for a more inclusive and compassionate education.